Statistical Investigation of the Efficiency of EMIC Waves in Precipitating Relativistic Electrons. Issue 8 (4th August 2018) - Qin, Murong; Hudson, Mary; Millan, Robyn; Woodger, Leslie; Shekhar, Sapna
Abstract: Electromagnetic ion cyclotron (EMIC) waves have been proposed to cause relativistic electron precipitation (REP). In our study, we carry out 4 years of analysis from 2013 to 2016, with REP spikes obtained from POES satellites and EMIC waves observation from Van Allen Probes. Among the 473 coincidence events when POES satellites go through the region conjugate to EMIC wave activity, only 127 are associated with REP. Additionally, the coincidence occurrence rate is about 10% higher than the random coincidence occurrence rate, indicating that EMIC waves and relativistic electrons can be statistically related, but the link is weaker than expected. H + band EMIC waves have been regarded as less important than He + band EMIC waves for the precipitation of relativistic electrons. We demonstrate that the proportion of H + band EMIC wave events that are associated with REP (22% to 32%) is slightly higher than for He + band EMIC wave activity (18% to 27%). An even greater proportion (25% to 40%) of EMIC waves are accompanied by REP events when H + band and He + band EMIC waves occur simultaneously. Key Points: Only 127 out of 473 EMIC wave events are associated with REP when POES satellites go through the region conjugate to EMIC wave activity The coincidence occurrence rate is about 10% higher than the random coincidence occurrence rate Proportion of EMIC wave events that are associated with REP: H + band and He + band waves occurring simultaneously >H + band >He + band